Childfree sebagai Hak Reproduksi: Analisis Perspektif Hak Asasi Manusia dan Gender Islam - Firdaus Jauhar Wicaksono; Arya Deny Widiyanto (Pro Justicia: Jurnal Hukum dan Sosial, 2026)
The childfree phenomenon of living has become increasingly prominent as part of broader social transformations regarding the meaning of family and reproductive rights. The decision not to have children constitutes a deliberate choice that often generates public debate, particularly in societies that continue to regard offspring as a core cultural and religious value. From a human rights perspective, the decision to have children or to remain childfree falls within the domain of individual rights protected by law. No legal provision mandates that couples must produce offspring. Within the framework of Islamic gender perspectives, reproductive rights are recognized as a shared responsibility between husband and wife. Islam affords women the space to refuse pregnancy as a means of safeguarding their well-being, health, and the biological and psychological burdens associated with reproduction. This study concludes that the choice to remain childfree is permissible within both Islamic teachings and human rights law, provided that the decision is made through mutual agreement between partners, supported by careful consideration, and grounded in full awareness of the responsibilities that accompany such a choice.